2008
DOI: 10.1093/cvr/cvn281
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular remodelling may induce cardiac dysfunction in congestive heart failure

Abstract: It is commonly held that cardiac remodelling, represented by changes in muscle mass, size, and shape of the heart, explains the progression of congestive heart failure (CHF). However, this concept does not provide any clear information regarding the development of cardiac dysfunction in CHF. Extensive research has revealed that various subcellular organelles such as the extracellular matrix, sarcolemma, sarcoplasmic reticulum, myofibrils, mitochondria, and nucleus undergo varying degrees of changes in their bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
123
0
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(133 citation statements)
references
References 125 publications
5
123
0
5
Order By: Relevance
“…[10][11][12] Several recent studies have demonstrated that the redox-sensitive changes in biochemical compositions, as well as architecture and functions of subcellular organelles, including the mitochondria, 13 ER, 14 and nucleus, 15 underpin phenotypic trait of cardiovascular diseases. Of note is a recent demonstration 14 that oxidative stress causes ER stress, with subsequent activation of UPR, leading to tissue damage and manifestation of myocardial dysfunction.…”
mentioning
confidence: 99%
“…[10][11][12] Several recent studies have demonstrated that the redox-sensitive changes in biochemical compositions, as well as architecture and functions of subcellular organelles, including the mitochondria, 13 ER, 14 and nucleus, 15 underpin phenotypic trait of cardiovascular diseases. Of note is a recent demonstration 14 that oxidative stress causes ER stress, with subsequent activation of UPR, leading to tissue damage and manifestation of myocardial dysfunction.…”
mentioning
confidence: 99%
“…proceso resulta en mayor prevalencia de ruptura ventricular, aneurismas y arritmias malignas. Adicionalmente, la remodelación está relacionada a la aparición y la progresión de la disfunción ventricular [1][2][3][4][5][6][7] . Debemos tener en cuenta que una de las estrategias más utilizadas para el estudio de la remodelación resultante de la oclusión coronaria es el modelo del infarto experimental en el ratón.…”
Section: Introductionunclassified
“…Adicionalmente, la remodelación está relacionada a la aparición y la progresión de la disfunción ventricular [1][2][3][4][5][6][7] .…”
unclassified
“…Previous studies have revealed varying degrees of depression in gene expression for SL, SR and MF proteins, as well as defects in subcellular organelles during the development of heart failure in patients and experimental animal models (1)(2)(3)(4)(5)(6). Accordingly, it has been suggested that cardiac dysfunction in failing hearts is due to subcellular remodelling as a consequence of changes in cardiac gene expression (2,(7)(8)(9).…”
mentioning
confidence: 99%